Clinical Holistic Medicine: Holistic Treatment of Children - Søren Ventegodt; Mohammed Morad; Gideon Vardi; Joav Merrick (The Scientific World Journal)
We believe a holistic approach to problems in childhood and adolescence will benefit the child, adolescent, and the whole family. As a rule, children have far less to say in the family than their parents. Therefore, it is the parents who set the agenda and decide how things are done at home and in relation to the child. Most often, it is also the parents who have a problem when the child is not thriving. The child thus acts as the thermometer of the family. When children are not feeling well or are sick, the parents are not doing well either. Most problems arising from dysfunctional patterns are almost impossible for the parents to solve on their own, but with help and support from the holistically oriented physician, we believe that many problems can be discovered and solved. Not only can health problems be addressed, but also problems of poor thriving in the family in general. With the physician in the role of a coach, the family can be provided with relevant exercises that will change the patterns of dysfunction. Consciousness-based medicine also seems to be efficient with children and adolescents, who are much more sensitive to the psychosocial dimensions than adults. Five needs seem to be essential for the thriving and health of the child: attention, respect, love, acceptance (touch), and acknowledgment. The physician should be able to see if the child lacks fulfillment in one or more of these needs, and he can then demonstrate to the parents how these needs should be handled. This should be followed by simple instructions and exercises for the parents in the spirit of coaching. This approach is especially relevant when the child is chronically ill.